Optimasi Produksi Terintegrasi: Peningkatan Produksi Minyak dan Gas di Lapangan X dengan Menggunakan Metode Gas Lift - Novriwanda
Increasing production of oil and gas wells in a field must consider integrated components. These components start from the reservoir, ending with the separator. It should consider restrictions that occur for each component so that the production rate from the field will be more realistic. Artificial Lift methods are often chosen as an alternative in increasing production in an Oil and Gas field. In this case study, an integrated model was developed for the offshore field with the condition that there are two reservoirs, five wells, and each well flowing naturally. The selection of Artificial Lift Methods in this field considers the condition of existing wells. The injection valve for Gas Lift has been installed for each well when the first completion of the well is carried out. So that the Artificial Lifting method used is Gas Lift Method. Gas injection is done to see how much production increases in this field. Optimal conditions are obtained by optimizing the gas injection for each well. In this study it was produced that Gas Lift injection was carried out on four of the five wells while one other well was allowed to flow naturally due to the improper condition of the well to do Gas Lift. Oil production in this field can be increased by 7%, which is from 14498 bopd to 15528 bopd.